Overstrength factors of RC bridges supported on single and multi-column RC piers in Mexico - Alma R. Sánchez (2021)
Mexico highway network has more than 14,000 bridges. Most of them are reinforced concrete (RC) structures. The bridges design process incorporates the use of an overstrength factor that is not justified and has received little attention in published works. Mexican regulations allow using an overstrength factor for buildings in the range of 2-3, to reduce the design spectra as a function of the selected seismic behavior factor. However, for bridges, a single factor of 1.5 is proposed independent of any design parameter. The bridges inMexico are mostly simply supported structureswithmaximum span lengths of 50 m. A relevant and distinctive aspect of the bridges designed in Mexico is the large load amplitudes of the trucks used to define the live load and the high seismic activity in the country. This study determines overstrength factors of a family of medium-length RC bridges composed of simply supported superstructures and substructure made up of single and multi-column RC piers. Non-linear dynamic analyzes using a set of 80 accelerograms were carried out. The results show that the height of the bridges and their seismic location are relevant parameters in the overstrength of the structures. Finally, analytical expressions are proposed to assess the overstrength factors of a very common bridge typology in Mexico and the world.